2009
DOI: 10.1038/nn.2287
|View full text |Cite
|
Sign up to set email alerts
|

Proteoglycan interactions with Sonic Hedgehog specify mitogenic responses

Abstract: SUMMARY Sonic Hedgehog (Shh) has dual roles in vertebrate development, as it promotes progenitor cell proliferation and induces tissue patterning. Here we show mitogenic and patterning functions of Shh can be uncoupled from one another. Using a genetic approach to selectively inhibit Shh-proteoglycan interactions in a mouse model, we show binding of Shh to proteoglycans is required for proliferation of neural stem/precursor cells but not for tissue patterning. Shh-proteoglycan interactions regulate both spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
80
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 50 publications
(90 reference statements)
5
80
0
Order By: Relevance
“…Much data have subsequently been compiled showing that this is only one of a number of cationic sequences that can bind glycosaminoglycans (38). The importance of the Lys-32-38 region in Shh for binding heparin and HS has been demonstrated (38). Our molecular modeling of murine Shh, however, suggested that another lysine residue 179 on the surface of Shh (Lys-178 in the human sequence) may also contribute to overall affinity of the morphogen for heparin.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Much data have subsequently been compiled showing that this is only one of a number of cationic sequences that can bind glycosaminoglycans (38). The importance of the Lys-32-38 region in Shh for binding heparin and HS has been demonstrated (38). Our molecular modeling of murine Shh, however, suggested that another lysine residue 179 on the surface of Shh (Lys-178 in the human sequence) may also contribute to overall affinity of the morphogen for heparin.…”
Section: Discussionmentioning
confidence: 97%
“…This region (Lys-32-38) precisely coincides with a consensus sequence for heparin binding, known as the Cardin-Weintraub motif (23). Much data have subsequently been compiled showing that this is only one of a number of cationic sequences that can bind glycosaminoglycans (38). The importance of the Lys-32-38 region in Shh for binding heparin and HS has been demonstrated (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HS expression and Dally-like/glypican expression are also essential for signal reception and modulation on Ptc-expressing receiving cells (10 -14) and participate in HhNp-Ihog interaction (15). However, the essential role of direct morphogen-HSPG interactions in embryonic patterning was recently challenged (16). In that report, transgenic mice made deficient in two ShhNp CW amino acid residues implicated in HS binding (17) lacked an Shh-related phenotype, suggesting that direct morphogen-HS interactions were not essential for normal development.…”
mentioning
confidence: 99%
“…Ligand-dependent activation of Hh signaling is associated with tumorigenesis in a subset of epithelial cancers, including colon, pancreatic and ovarian cancer (Theunissen and de Sauvage, 2009), and HSPGs regulate Shh activity and Shh-dependent cancer cell proliferation (Chan et al, 2009). Importantly, Hh does not activate autocrine cancer cell signaling, but instead signals to the stromal compartment (Tian et al, 2009;Yauch et al, 2008), which in turn provides a more favorable environment for tumor growth.…”
Section: The Heparan Sulfate Source Determines Shh Processingmentioning
confidence: 99%